Seismic Performance of Reinforced Concrete Coupled Walls with Segmental Coupling Beams - Xiaobin Hu; Qinwang Lu; Zihao Xu; Shen Zhang (Advances in Civil Engineering, 2019)
A novel reinforced concrete (RC) segmental coupling beam (SCB), which mainly comprises the energy dissipating (ED) segment and load bearing (LB) segment, is proposed in this paper. In order to examine its applicability in engineering practice, one scaled RC coupled wall specimen with the proposed SCBs was constructed and experimentally investigated under cyclic loading. The results show that both cracking and yielding occurred much earlier on the ED segments of the SCBs compared to the LB segments. In addition, a lot more cracks distributed densely on the ED segments were observed at the end of the test. It demonstrates that the ED segments play a main role in the energy dissipation, while the LB segments are always reliably capable of carrying the gravity load transferred from the floor beams. Finally, the finite element analysis model of the RC coupled wall is established and validated by comparing the analysis results with the experimental ones. Utilizing the proposed analysis model, parametric analyses are conducted to investigate the influence of a variety of design parameters, including the axial compressive ratio of the wall pier, concrete strength, and especially sectional height of the SCB, on seismic performance of the coupled wall. It shows that as the sectional height of the ED segment increases, the energy dissipating capacity of the coupled wall may improve while the ability of supporting the gravity load is lowered.